Single-layer aluminum alloy material for brazing, method for producing same, aluminum structure, and heat exchanger

By adjusting the content and proportions of Si, Fe, Cu, Mn and Zn in the aluminum alloy material, the problem of insufficient brazing and corrosion resistance of existing aluminum alloy materials at high temperatures is solved, and excellent brazing and High temperature strength and improve the corrosion resistance of aluminum structures.

CN119301285APending Publication Date: 2025-01-10UACJ CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046880.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing aluminum alloy materials have shortcomings in brazing and corrosion resistance at high temperatures, especially in terms of improving strength and corrosion resistance while ensuring brazing properties.

Method used

A single-layer aluminum alloy material using specific chemical components contains Si: 2.0% to 3.0%, Fe: 0.05% to 0.40%, Cu: 0.05% to 0.25%, Mn: 0.8% to 1.6%, Zn: 1.0% to 3.0 %, and meets the specific ranges of Fe/Cu ratio, Fe+Cu total and Cu/Zn ratio to improve brazing properties and high temperature strength, while enhancing the corrosion resistance of aluminum structures.

Benefits of technology

Excellent brazing properties, strength at high temperatures and corrosion resistance of aluminum structures are achieved, avoiding the problem of reducing strength and corrosion resistance during brazing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301285A_ABST
    Figure CN119301285A_ABST
Patent Text Reader

Abstract

A single-layer aluminum alloy material (1) for brazing has a chemical composition containing 2.0 mass% to 3.0 mass% (inclusive) of Si, 0.05 mass% to 0.40 mass% (inclusive) of Fe, 0.05 mass% to 0.25 mass% (inclusive) of Cu, 0.8 mass% to 1.6 mass% (inclusive) of Mn, and 1.0 mass% to 3.0 mass% (inclusive) of Zn, with the remainder comprising Al and unavoidable impurities, and the ratio of the Fe content to the Cu content, namely Fe / Cu, is 1.2 to 5.0 (inclusive). The total of the content of Fe and the content of Cu is 0.25 mass% or more and 0.65 mass% or less, and the ratio of the content of Cu to the content of Zn, Cu / Zn, is 0.02 or more and 0.40 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a single-layer aluminum alloy material for brazing, a manufacturing method thereof, an aluminum structure and a heat exchanger. Background Art

[0002] For example, aluminum products such as heat exchangers have multiple components made of aluminum or aluminum alloys. These components are sometimes joined to each other via brazing. In the past, the following methods are known as methods for brazing the constituent components of aluminum products: a method of arranging a brazing filler metal on a portion to be brazed, a method of applying a brazing paste containing Si powder to a portion to be brazed and generating a brazing filler metal from a constituent component using the brazing paste, a method of brazing using a brazing plate having a core material and a brazing filler metal provided on at least one surface of the core material, and the like.

[0003] In addition, in recent years, a single-layer aluminum alloy material has been proposed, which is configured to generate a trace amount of molten metal by heating and can be brazed with an object material. As such an aluminum alloy material, for example, Patent Document 1 describes a single-layer aluminum alloy material, which contains Si: 1.0 mass% to 5.0 mass%, Fe: 0.01 mass% to 2.0 mass%, and one or more selected from Mg: 2.0 mass% or less, Cu: 1.5 mass% or less, and Mn: 2.0 mass% or less, and the remainder is composed of Al and unavoidable impurities.

[0004] Prior Art Literature Patent Literature Patent Document 1: Japanese Patent No. 5337326 Summary of the invention

[0005] Technical problem to be solved by the invention However, the aluminum alloy material of Patent Document 1 still has room for improvement in terms of improving the strength at high temperatures while ensuring brazing properties, and in terms of further improving the corrosion resistance of an aluminum structure including the aluminum alloy material.

[0006] The present invention is completed in view of this background, and its purpose is to provide a single-layer aluminum alloy material for brazing that has excellent brazing properties, high strength at high temperatures, and can improve the corrosion resistance of the aluminum structure, and a method for manufacturing the same, as well as an aluminum structure and a heat exchanger having the single-layer aluminum alloy material for brazing.

[0007] Technical solutions for solving technical problems One embodiment of the present invention is a single-layer aluminum alloy material for brazing, which has the following chemical composition: Si (silicon): 2.0 mass% to 3.0 mass% inclusive, Fe (iron): 0.05 mass% to 0.40 mass% inclusive, Cu (copper): 0.05 mass% to 0.25 mass% inclusive, Mn (manganese): 0.8 mass% to 1.6 mass% inclusive, Zn (zinc): 1.0 mass% to 3.0 mass% inclusive, and the remainder is Al (aluminum) and unavoidable impurities. The ratio of the Fe content to the Cu content is 1.2 or more and 5.0 or less, The total of the Fe content and the Cu content is 0.25 mass % or more and 0.65 mass % or less, The ratio of the Cu content to the Zn content is 0.02 or more and 0.40 or less.

[0008] Effects of the Invention The single-layer aluminum alloy material for brazing (hereinafter referred to as "aluminum material" or "aluminum alloy material") has the following chemical composition: in addition to the contents of Si, Fe, Cu, Mn and Zn being within the specific ranges, the ratio of the content of Fe to the content of Cu, the total of the content of Fe and the content of Cu, and the ratio of the content of Cu to the content of Zn are within the specific ranges. As a result, the aluminum material can improve the brazing property, the strength at high temperature, and the corrosion resistance of the aluminum structure in a balanced manner.

[0009] Therefore, according to the above aspect, it is possible to provide a single-layer aluminum alloy material for brazing that has excellent brazing properties, has high strength at high temperatures, and can improve the corrosion resistance of an aluminum structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a cross-sectional view of a single-layer aluminum alloy material for brazing in an example.

[0011] Figure 2 This is a perspective view of a micro-core test body in the example.

[0012] Figure 3 This is an explanatory diagram of a device for measuring the spontaneous electrode potential in the example. DETAILED DESCRIPTION

[0013] (Single-layer aluminum alloy material for brazing) The single-layer aluminum alloy material for brazing is composed of a single layer of an aluminum alloy having the above chemical composition. The chemical composition of the aluminum material and the reasons for its limitation are described below.

[0014] ·Si The aluminum material contains Si in an amount of 2.0% by mass or more and 3.0% by mass or less as an essential component. By setting the Si content in the aluminum material to 2.0% by mass or more, a molten metal containing Al and Si can be generated by brazing heating, and the aluminum material can be joined to a target material. The Si content is preferably 2.2% by mass or more, and more preferably 2.3% by mass or more. In this case, the amount of molten metal generated by brazing heating can be increased, further improving the brazing property. When the Si content is less than 2.0% by mass, the amount of molten metal generated by brazing heating is insufficient, which may lead to deterioration of the brazing property.

[0015] On the other hand, if the Si content is too high, the amount of aluminum material dissolved during brazing heating increases, which may lead to a decrease in the strength of the aluminum material. As a result, the shape of the structure containing the aluminum material may not be maintained during brazing. From the viewpoint of avoiding this problem, the Si content is set to 3.0 mass % or less. From the same viewpoint, the Si content is preferably 2.8 mass % or less, and more preferably 2.6 mass % or less.

[0016] In order to ensure the strength of the aluminum material during brazing and improve brazing properties, the Si content is preferably 2.2 mass % to 2.8 mass %, and more preferably 2.3 mass % to 2.6 mass %.

[0017] ·Fe, Cu, Zn The aluminum material contains, as essential components, 0.05 mass % or more and 0.40 mass % or less of Fe, 0.05 mass % or more and 0.25 mass % or less of Cu, and 1.0 mass % or more and 3.0 mass % or less of Zn. In addition, the contents of Fe, Cu, and Zn satisfy the following three relationships: (1) the ratio of the content of Fe to the content of Cu (i.e., the value of Fe / Cu) is 1.2 or more and 5.0 or less; (2) the total content of Fe and the content of Cu (i.e., the value of Fe+Cu) is 0.25 mass % or more and 0.65 mass % or less; and (3) the ratio of the content of Cu to the content of Zn (i.e., the value of Cu / Zn) is 0.02 or more and 0.40 or less.

[0018] A part of Fe is dissolved in the Al matrix and has the effect of improving the strength of the aluminum material. In addition, the remaining part of Fe is dispersed in the Al matrix as a crystal, which has the effect of improving the strength of the aluminum material at room temperature and high temperature. Moreover, Fe has the effect of refining the crystal grains of the aluminum material. By refining the crystal grains of the aluminum material, the molten metal can easily seep out from the grain boundaries during brazing heating, which can improve the brazing performance. However, if the Fe content is too much, coarse intermetallic compounds are easily formed during casting, which may lead to a decrease in the manufacturability of the aluminum material.

[0019] On the other hand, Cu also dissolves in the Al matrix and has the effect of increasing the strength of the aluminum material. In addition, Cu, like Fe, has the effect of refining the grains of the aluminum material. However, if the Cu content is too high, the amount of molten metal generated by the aluminum material during brazing heating is too high, which may lead to a decrease in strength at high temperatures. In addition, in this case, the potential of the aluminum material increases, which may also lead to a decrease in the corrosion resistance of the aluminum structure containing the aluminum material.

[0020] Therefore, by setting the content of Fe and the content of Cu to the specific ranges, and further setting the ratio of the content of Fe to the content of Cu and the total content of Fe and Cu to the specific range, it is possible to avoid a decrease in the manufacturability of the aluminum material, avoid a decrease in the corrosion resistance of the aluminum structure, and improve the strength of the aluminum material at high temperatures. From the viewpoint of more reliably obtaining this effect, the ratio of the content of Fe to the content of Cu is preferably 1.2 or more and 4.0 or less.

[0021] On the other hand, for example, when the aluminum material is used as a fin for a heat exchanger, the fin after brazing is sometimes processed. However, if the strength of the aluminum material after brazing is too high, it is possible to reduce the formability. From the viewpoint of more easily avoiding this problem, the total content of Fe and the content of Cu is preferably 0.25 mass % or more and 0.60 mass % or less, more preferably 0.25 mass % or more and 0.55 mass % or less, and further preferably 0.25 mass % or more and 0.50 mass % or less.

[0022] In addition, Cu is effective for improving brazing properties and the strength of aluminum materials as described above, and on the other hand, it has the effect of increasing the potential of aluminum materials. Therefore, if the Cu content is too high, the aluminum material cannot function as a sacrificial anode, and there is a possibility that the corrosion resistance of the aluminum structure is reduced, and the brazing joint formed between the aluminum material and the counterpart material is easily corroded.

[0023] On the other hand, Zn also has the effect of increasing the amount of molten metal generated by the aluminum material. Furthermore, Zn has the effect of lowering the potential of the aluminum material, so by adding Zn together with Cu, it is possible to avoid excessive increase in the potential of the aluminum material and improve brazing properties. However, if the Zn content is too high, the potential of the aluminum material is excessively lowered, and the aluminum material itself may be easily corroded.

[0024] Therefore, by setting the content of Cu and the content of Zn to the specific ranges, and further setting the ratio of the content of Cu to the content of Zn to the specific range, it is possible to avoid a decrease in the corrosion resistance of the aluminum structure and a decrease in the corrosion resistance itself, and to improve brazing properties. From the viewpoint of more reliably obtaining this effect, the ratio of the content of Cu to the content of Zn is preferably 0.02 or more and 0.10 or less, and more preferably 0.02 or more and 0.08 or less.

[0025] As described above, by making the contents of Fe, Cu and Zn within the specific ranges and further making the contents of Fe, Cu and Zn satisfy the relationships (1) to (3) above, the brazing properties of the aluminum material, the strength at high temperatures and the corrosion resistance of the aluminum structure can be improved in a balanced manner.

[0026] ·Mn The aluminum material contains 0.8 mass % or more and 1.6 mass % or less of Mn as an essential component. A portion of Mn forms an Al-Mn-Si-based intermetallic compound in the aluminum material, which has the effect of improving the strength of the aluminum material by dispersion strengthening. In addition, the remaining portion of Mn is solid-dissolved in the Al matrix, which has the effect of improving the strength of the aluminum material by solid solution strengthening.

[0027] By setting the content of Mn in the aluminum material to 0.8% by mass or more, the strength of the aluminum material can be improved by dispersion strengthening and solid solution strengthening. Moreover, for the aluminum material, the aforementioned dispersion strengthening and solid solution strengthening can suppress the decrease in strength during brazing heating, and suppress the deformation and buckling of the aluminum material. When the content of Mn is less than 0.8% by mass, the effect of improving the strength by Mn is reduced, and the deformation and buckling of the aluminum material may easily occur.

[0028] On the other hand, when the content of Mn is too high, coarse intermetallic compounds are easily formed during the manufacturing process of the aluminum material. If rolling is performed in a state containing such coarse intermetallic compounds, pinholes may be easily generated. From the viewpoint of easily avoiding this problem, the content of Mg is set to 1.6 mass % or less.

[0029] The aluminum material may contain, in addition to the aforementioned essential components, Al, and unavoidable impurities, elements such as Mg (magnesium), Cr (chromium), Ti (titanium), Zr (zirconium), In (indium), Sn (tin), V (vanadium), Ni (nickel), Be (beryllium), Sr (strontium), Bi (bismuth), and Na (sodium) as arbitrary components.

[0030] Mg The aluminum material may contain Mg in an amount exceeding 0% by mass and below 2.0% by mass as an arbitrary component. Mg forms Mg2Si in the aluminum material after brazing, which has the effect of improving the strength of the aluminum material through aging hardening. On the other hand, if the Mg content is too high, when brazing is performed using a flux, Mg reacts with the flux, which may lead to a decrease in brazing properties. By setting the Mg content to be greater than 0% by mass and below 2.0% by mass, this problem can be easily avoided and the strength of the aluminum material can be improved.

[0031] ·Cr The aluminum material may contain more than 0 mass % and less than 0.3 mass % Cr as an arbitrary component. A part of Cr forms an Al-Cr intermetallic compound in the aluminum material, which has the effect of improving the strength of the aluminum material by dispersion strengthening. In addition, the remaining part of Cr is solid-dissolved in the Al matrix, which has the effect of improving the strength of the aluminum material by solid solution strengthening. On the other hand, if the Cr content is too much, it is easy to form a coarse intermetallic compound in the manufacturing process of the aluminum material, which may lead to a decrease in plastic workability.

[0032] By setting the Cr content in the aluminum material to the specific range, the formation of coarse Al-Cr intermetallic compounds can be avoided, and the strength of the aluminum material can be further improved by dispersion strengthening and solid solution strengthening.

[0033] Ti, V The aluminum material may contain, as an arbitrary component, one or both of Ti in an amount exceeding 0% by mass and below 0.3% by mass and V in an amount exceeding 0% by mass and below 0.3% by mass. Ti and V are solid-dissolved in the Al matrix and have the effect of improving the strength of the aluminum material. In addition, Ti and V are distributed in layers in the aluminum material, and have the effect of inhibiting the development of corrosion in the thickness direction of the aluminum material. On the other hand, if the content of Ti or the content of V is too much, huge crystals are easily formed during the manufacturing process of the aluminum material, which may lead to a reduction in plastic workability.

[0034] By setting the Ti content and the V content in the aluminum material to be within the specific ranges, the formation of giant crystals can be avoided, and the strength and self-corrosion resistance of the aluminum material can be further improved.

[0035] ·Zr The aluminum material may contain Zr in an amount exceeding 0 mass % and below 0.3 mass % as an arbitrary component. Zr forms an Al-Zr-based intermetallic compound in the aluminum material, which has the effect of increasing the strength of the aluminum material by dispersion strengthening. In addition, the Al-Zr-based intermetallic compound has the effect of coarsening the grains of the aluminum material during brazing heating. On the other hand, if the Zr content is too high, coarse intermetallic compounds are easily formed during the manufacturing process of the aluminum material, which may lead to a decrease in plastic workability.

[0036] By setting the Zr content in the aluminum material to be within the specific range, the formation of coarse intermetallic compounds can be avoided and the above-mentioned effects can be obtained.

[0037] Sn、In The aluminum material may contain, as an arbitrary component, one or both of Sn in an amount of more than 0 mass % and less than 0.3 mass % and In in an amount of more than 0 mass % and less than 0.3 mass %. Sn and In, like Zn, have the effect of lowering the potential of the aluminum material. By setting the content of Sn and the content of In in the aluminum material to the specific range, it is possible to avoid a decrease in the corrosion resistance of the aluminum material and adjust the potential of the aluminum material, thereby further improving the corrosion resistance of the aluminum structure.

[0038] ·Ni The aluminum material may contain Ni in an amount exceeding 0% by mass and below 2.0% by mass as an arbitrary component. Ni forms intermetallic compounds in the aluminum material, which has the effect of improving the strength of the aluminum material after brazing by dispersion strengthening. On the other hand, if the Ni content is too much, coarse intermetallic compounds are easily formed during the manufacturing process of the aluminum material, which may lead to a decrease in plastic workability. In addition, in this case, the corrosion resistance of the aluminum material itself may also be reduced. By setting the Ni content in the aluminum material to more than 0% by mass and below 2.0% by mass, preferably to more than 0.05% by mass and below 2.0% by mass, the aforementioned problems can be easily avoided and the strength of the aluminum material can be further improved.

[0039] ·Be, Sr, Bi, Na The aluminum material may contain one or more of more than 0% by mass and less than 0.3% by mass of Be, more than 0% by mass and less than 0.3% by mass of Sr, more than 0% by mass and less than 0.3% by mass of Bi, and more than 0% by mass and less than 0.3% by mass of Na. These elements refine Si particles in the aluminum material and improve the fluidity of the molten metal produced by the aluminum material during brazing heating, thereby improving brazing properties. On the other hand, when the content of these elements is too high, the corrosion resistance of the aluminum material may be reduced.

[0040] By setting the Be content, the Sr content, the Bi content, and the Na content to the specific ranges, respectively, it is possible to avoid a decrease in corrosion resistance and further improve the brazing properties of the aluminum material.

[0041] Metal structure The aluminum material has a metal structure composed of a non-fibrous structure. It should be noted that the non-fibrous structure refers to a structure other than a fibrous structure (i.e., a structure composed of fibrous crystal grains formed by stretching and extending in a processing direction). The non-fibrous structure includes, for example, a structure composed of granular crystal grains. A person skilled in the art can easily determine whether the metal structure of the aluminum material is a non-fibrous structure.

[0042] The average grain size of the aluminum material is preferably 100 μ m or more and 1000 μ m or less, more preferably 200 μ m and above and 900 μ m or less. In this case, the number density of the grain boundaries in the aluminum material can be appropriately increased. When the aluminum material is joined to the counterpart material, the molten liquid generated by the aluminum material mainly moves inside the aluminum material via the grain boundaries and is supplied to the surface of the aluminum material. Therefore, by appropriately increasing the number density of the grain boundaries in the aluminum material, the brazing property of the aluminum material can be further improved.

[0043] (Manufacturing method) The aluminum material may be manufactured in various ways. For example, the aluminum material may be an extended material obtained by an extension process, or a forged material obtained by a forging process. In addition, the aluminum material may be a casting obtained by casting.

[0044] From the viewpoint of improving brazing property and strength, the aluminum material is preferably a ductile material. The degree of processing in the manufacturing process of the ductile material is greater than that in the manufacturing process of the forged material, casting, etc., so the second phase particles are easily cut off during the manufacturing process. Therefore, the aluminum material composed of the ductile material can make the number of Si particles, Si-based intermetallic compounds, Al-based intermetallic compounds, etc. dispersed in the Al matrix larger. As a result, the brazing property and strength can be improved in a balanced manner.

[0045] When the aluminum material composed of an extended material is produced, for example, a continuous casting method such as a twin-roller continuous casting rolling method or a twin-belt continuous casting method can be used. Compared with the DC casting method, the continuous casting method can increase the cooling rate during casting. Therefore, a plurality of fine Si particles and other second phase particles can be formed in the aluminum material. In addition, by dispersing a plurality of fine second phase particles in the aluminum material, the amount of the molten metal formed during brazing heating can be increased, thereby improving brazing properties.

[0046] When the aluminum material is produced by a twin-roll continuous casting and rolling method, the casting speed is preferably set to 0.5 m / min or more and 3 m / min or less. In the twin-roll continuous casting and rolling method, by setting the casting speed to 0.5 m / min or more, the cooling rate during casting can be fully increased, and the second phase particles in the aluminum material can be easily refined. In addition, by setting the casting speed to 3 m / min or less, the molten metal can be fully cooled during casting to solidify it.

[0047] In addition, the temperature of the molten metal during casting is preferably 650°C or higher and 800°C or lower, and more preferably 680°C or higher and 750°C or lower. By setting the temperature of the molten metal to preferably 650°C or higher, and more preferably 680°C or higher, it is possible to avoid the formation of huge crystals in the molten metal. In addition, by setting the temperature of the molten metal to preferably 800°C or lower, and more preferably 750°C or lower, the molten metal can be sufficiently cooled and solidified during casting.

[0048] The thickness of the rolled plate obtained by casting is preferably 2 mm or more and 10 mm or less, more preferably 4 mm or more and 8 mm or less. By making the thickness of the rolled plate preferably 2 mm or more, more preferably 4 mm or more, a healthy rolled plate can be stably manufactured. In addition, by making the thickness of the rolled plate preferably 10 mm or less, more preferably 8 mm or less, it is easy to wind the rolled plate after casting on a roller.

[0049] The rolled plate obtained by the continuous casting method can be used directly as the aluminum material. In addition, by adjusting the thickness and material of the rolled plate by cold rolling, heat treatment, etc., the aluminum material with the desired thickness and material can also be obtained. The aluminum material can, for example, have a material represented by a material mark O, H1n or H2n. From the viewpoint of suppressing corrosion during brazing, the aluminum material preferably has a material represented by a material mark H1n or H2n.

[0050] In addition, the aluminum material composed of an extended material can be produced, for example, by a method of performing an extension process on the ingot after producing the ingot by DC casting. When the ingot is produced by DC casting, the casting speed is preferably 20 mm / minute or more and 100 mm / minute or less, and more preferably 30 mm / minute or more and 80 mm / minute or less. In DC casting, by setting the casting speed preferably to 20 mm / minute or more, and more preferably to 30 mm / minute or more, the cooling rate during casting can be sufficiently increased, and the second phase particles in the aluminum material can be easily refined. In addition, by setting the casting speed preferably to 100 mm / minute or less, and more preferably to 80 mm / minute or less, the molten metal can be sufficiently cooled and solidified during casting.

[0051] When the slab is produced by DC casting, the thickness of the slab is preferably 600 mm or less, and more preferably 500 mm or less. In this case, the cooling rate during casting can be sufficiently increased, and the second phase particles in the aluminum material can be easily refined.

[0052] After the ingot is made by DC casting, the ingot is extended, thereby obtaining an aluminum material having a desired shape. For example, after the slab is made in DC casting, the slab is rolled, thereby obtaining the aluminum material consisting of a rolled plate having a desired thickness. As the rolling process, hot rolling and cold rolling can be appropriately combined. In addition, from before the rolling process to after the rolling process is completed, heat treatments such as homogenization and annealing can be performed as needed to adjust the material of the aluminum material. The aluminum material can, for example, have a material represented by a material mark O, H1n or H2n. From the viewpoint of suppressing corrosion during brazing, the aluminum material preferably has a material represented by a material mark H1n or H2n.

[0053] In addition, after the billet is produced in DC casting, the billet is subjected to hot extrusion processing to obtain the aluminum material composed of an extruded material having a desired cross-sectional shape. Before hot extrusion processing, the billet can be subjected to homogenization treatment as needed. The billet is cast by a casting method such as hot top casting or GDC casting.

[0054] In the manufacturing method, new aluminum ingots, intermediate alloys, and aluminum scraps can be used as casting raw materials during casting. The aluminum scraps used as casting raw materials include, for example, discarded aluminum products, aluminum parts separated from discarded products, and scraps and chips generated in the manufacturing process of aluminum products and aluminum parts. When using aluminum scrap as a casting raw material, the aluminum scrap can be directly melted. In addition, the aluminum scrap can be melted after adjusting the size of the aluminum scrap by cutting and compressing the aluminum scrap. Moreover, after temporarily making a recycled aluminum ingot from the aluminum scrap, the recycled aluminum ingot can be used as a casting raw material.

[0055] (Aluminum structure) The aluminum material and the counterpart material are brazed to obtain an aluminum structure. That is, the aluminum structure includes the aluminum material, the counterpart material to be joined to the aluminum material, and the brazed joint formed between the aluminum material and the counterpart material.

[0056] The counterpart material to be joined to the aluminum material may be made of aluminum or an aluminum alloy. For example, the counterpart material may be a single-layer material made of aluminum or an aluminum alloy that cannot be brazed by itself. In addition, the single-layer aluminum alloy material for brazing may also be used as the counterpart material.

[0057] The use of the aluminum structure is not particularly limited. For example, the aluminum structure can be configured as a heat exchanger. The heat exchanger can be, for example, a condenser or an evaporator assembled in an air conditioner and used for heat exchange between a heat transfer medium and external air. In addition, the heat exchanger can be, for example, a radiator or an oil cooler assembled in an automobile.

[0058] The heat exchanger has various components such as tubes for circulating the heat transfer medium, fins for expanding the heat exchange area, tanks and plates for distributing the heat transfer medium to a plurality of tubes or collecting the heat transfer medium derived from the tubes, etc., depending on its purpose and use conditions. At least one of these components may be made of the aluminum material.

[0059] For example, the tubes made of the aluminum material and the corrugated fins made of the aluminum material are alternately stacked, and the plates made of the aluminum material are arranged on the outermost side in the stacking direction, thereby manufacturing a heat exchanger core. Next, tanks made of the aluminum material are installed at both ends of the plurality of tubes in the heat exchanger core, thereby manufacturing an assembly. By heating and brazing the assembly, a so-called parallel flow heat exchanger can be obtained.

[0060] In addition, in the aforementioned parallel flow heat exchanger, for example, as a tube, a tube made of an aluminum alloy that does not have the function of forming a brazing joint can be used instead of the tube made of the aluminum material. In this case, the tube may be an extruded material formed by extrusion processing, or may be an electric resistance welded tube formed by performing electric resistance welding (electric resistance welding) processing on a plate.

[0061] Furthermore, for example, by stacking two plates made of the aluminum material and having recessed portions so as to form a flow path for the heat transfer medium between the two plates, and then brazing them, a so-called laminated heat exchanger can be obtained.

[0062] In addition, for example, a heat exchanger can be obtained by preparing a radiator made of the aluminum material and having a plurality of fins vertically arranged on a base plate and a cover made of the aluminum material and having a hollow portion, and joining the radiator to the hollow portion of the cover. Furthermore, an oil cooler can also be obtained by stacking the radiator and the cover.

[0063] When manufacturing an aluminum structure including the aluminum material, first, components of the aluminum structure including the aluminum material are prepared, and these components are assembled to manufacture an assembly. The assembly is heated to generate a molten metal from the aluminum material. Furthermore, a brazing joint is formed between the aluminum material and a target material, thereby obtaining an aluminum structure.

[0064] The heating temperature when the aluminum material is joined to the counterpart material is preferably set so that the liquid phase ratio of the aluminum material, that is, the ratio of the mass of the molten liquid generated by the aluminum material to the mass of the aluminum material before brazing heating is greater than 5% by mass and less than 35% by mass, and more preferably set to greater than 7% by mass and less than 25% by mass. By setting the liquid phase ratio of the aluminum material during heating to within the specific range, the reduction in the strength of the aluminum material during heating can be suppressed, and a sufficient amount of molten liquid can be generated from the aluminum material to easily form a brazing joint with the counterpart material.

[0065] In addition, the holding time of the heating temperature when the aluminum material is joined to the object material is preferably set to be 30 seconds or more and 3600 seconds or less, and more preferably set to be 60 seconds or more and 1800 seconds or less. By setting the holding time of the heating temperature of the aluminum material to be within the specific range, the reduction in the strength of the aluminum material during heating can be suppressed, and the molten metal generated by the aluminum material can be fully filled between the aluminum material and the object material. It should be noted that in the joining of the aluminum material and the object material, the molten metal is generated from the entire surface of the aluminum material, so the length of the holding time can be set regardless of the area of ​​the brazing joint formed between the aluminum material and the object material.

[0066] More specifically, for example, the heating temperature when joining the aluminum material to the object material can be appropriately set from a range of 580°C to 620°C. In addition, the holding time of the heating temperature can be appropriately set from a range of, for example, 0 minutes to 10 minutes, preferably 30 seconds to 5 minutes. Here, the holding time refers to the time elapsed from the moment when the heating temperature reaches the desired temperature. When the holding time of the heating temperature is 0 minutes, the heating is immediately terminated and the cooling of the aluminum structure is started after the heating temperature reaches the desired time.

[0067] The liquid phase ratio of the aluminum material can be determined based on the equilibrium diagram at the desired temperature and based on the lever rule. As the equilibrium diagram used for calculating the liquid phase ratio, a known equilibrium diagram can be used, or an equilibrium diagram created by software for calculating the equilibrium diagram can be used. As such software, for example, the thermodynamic calculation system "Thermo-Calc (registered trademark)" manufactured by Thermo-Calc Software AB can be used.

[0068] The atmosphere when the aluminum material is joined to the object material is not particularly limited, but is preferably a non-oxidizing atmosphere such as nitrogen or argon from the viewpoint of suppressing unnecessary oxidation of the aluminum structure. In addition, the aluminum material can also be joined to the object material by heating the assembly in a reduced pressure atmosphere.

[0069] From the viewpoint of further improving the brazing property of the aluminum material and the counterpart material, a flux may be pre-arranged at the portion of the assembly to be brazed, and then the assembly may be heated for brazing. As the flux, for example, a fluoride-based flux such as KAlF4, K2AlF5, K2AlF5·H2O, K3AlF6, AlF3, KZnF3, and K2SiF6, a cesium-based flux such as Cs3AlF6, CsAlF4·2H2O, and Cs2AlF5·H2O, a chloride-based flux, and other compounds used as flux for brazing aluminum may be used.

[0070] In addition, it is also possible to form a Zn spray coating, a flux containing Zn atoms, a Zn powder, a Zn coating, etc. on the surface of one or more of the constituent members of the aluminum structure in advance, and then heat it to join the aluminum material to the object material. In this case, the corrosion resistance of the aluminum structure can be further improved. From the same point of view, the aluminum structure after heating can also be subjected to surface treatment such as chromate treatment and non-chromate treatment.

[0071] Example The following is an example of the single-layer aluminum alloy material for brazing. The aluminum alloy material has the following chemical composition: containing Si: 2.0 mass % or more and 3.0 mass % or less, Fe: 0.05 mass % or more and 0.40 mass % or less, Cu: 0.05 mass % or more and 0.25 mass % or less, Mn: 0.8 mass % or more and 1.6 mass % or less, Zn: 1.0 mass % or more and 3.0 mass % or less, the remainder is composed of Al and unavoidable impurities, the content of Fe relative to the content of Cu is 1.2 or more and 5.0 or less, the total content of Fe and the content of Cu is 0.25 mass % or more and 0.65 mass % or less, and the content of Cu relative to the content of Zn is 0.02 or more and 0.40 or less. The more specific composition of the aluminum material is described below together with the manufacturing method.

[0072] like Figure 1 As shown, the aluminum material 1 of this example is a plate material of a single-layer structure composed of an aluminum alloy having the function of forming a brazing joint. In addition, the aluminum material 1 of this example has a metal structure composed of a non-fibrous structure. The aluminum material 1 can be produced, for example, by rolling a cast plate produced by a twin-roll continuous casting and rolling method. Specifically, first, a cast plate having the chemical composition shown in Table 1 is produced by a twin-roll continuous casting and rolling method. The temperature of the molten metal during casting can be appropriately set, for example, within the range of 650 to 800°C. There is no particular limitation on the size of the cast plate, for example, the thickness is 6 mm.

[0073] It should be noted that the symbol "Bal." in Table 1 represents the remainder. In addition, the "Fe / Cu" column in Table 1 records the ratio of the Fe content to the Cu content, the "Fe+Cu" column records the total of the Fe content and the Cu content, and the "Cu / Zn" column records the ratio of the Cu content to the Zn content.

[0074] Then, the cast plate is cold rolled to produce a rolled plate with a thickness of 0.100 mm. The rolled plate is kept at a temperature of 380°C for 3 hours for intermediate annealing, and is further cold rolled to reduce the thickness of the rolled plate to 0.070 mm. Through the above-mentioned process, the test materials S1 and S2 shown in Table 1 can be obtained. It should be noted that the test materials R1 and R2 shown in Table 1 are test materials for comparison with the test materials S1 and S2. The composition of the test materials R1 and R2 is the same as that of the test materials S1 and S2, except that they have the chemical composition shown in Table 1.

[0075] Next, the evaluation method of various properties of the aluminum material will be described.

[0076] Average grain size In the evaluation of the average grain size, the test piece before brazing heating and the test piece after brazing heating were prepared as follows. First, the test material was cut to collect a flat plate with a length of 300 mm and a width of 150 mm. A small piece with a length of 20 mm and a width of 15 mm was collected from the flat plate, and the small piece was used as the test piece before brazing heating.

[0077] A 300 mm long, 150 mm wide flat plate was prepared and kept at 580°C to 600°C for 3 minutes in a nitrogen atmosphere. A 20 mm long, 15 mm wide piece was collected from the heated flat plate and used as a test piece after brazing heating.

[0078] The test piece prepared as described above was ground in the thickness direction and then mirror-polished to expose the center plane in the thickness direction of the test piece. Then, the center plane was etched to make the grain boundary obvious, and then the center plane was observed using a polarizing microscope. Then, three evaluation areas were set on the part of the center plane representing the metal structure of the test piece, and polarizing microscope images of these areas were obtained. It should be noted that the magnification of the polarizing microscope was 50 times.

[0079] Using the polarizing microscope image obtained in this way, the average grain size of the test material is calculated by the cutting method specified in JIS G0551 (2020). Specifically, a circle with a diameter of 79.58 mm, a circle with a diameter of 53.05 mm, and a circle with a diameter of 26.53 mm with a common center are drawn on the polarizing microscope image, and the number of grains intersecting these circles is counted. Then, the value obtained by dividing the sum of the lengths of the circumferences of the above three circles by the number of grains is taken as the average grain size. That is, the average grain size d (unit: μ m) is expressed by the following formula using the number n (unit: piece) of crystal grains intersecting the circle and the observation magnification X (unit: times) of a polarizing microscope.

[0080] d=1000π(79.58+53.05+26.53) / nX Table 2 shows the average crystal grain sizes of the test pieces before brazing heating and the test pieces after brazing heating.

[0081] ·Tensile strength of aluminum before brazing Using each test material, a tensile test was performed according to a method based on JIS Z2241: 2011. It should be noted that the tensile speed in the tensile test was 10 mm / min and the gauge length was 50 mm. The tensile strength of the test material was determined based on the stress-strain curve obtained by the tensile test. Table 2 shows the tensile strength of the test material before brazing heating.

[0082] Tensile strength of aluminum after brazing The test material was kept at a temperature of 580°C to 600°C for 3 minutes in a nitrogen atmosphere, and a tensile test was performed by a method based on JIS Z2241:2011 using the test material after heating equivalent to brazing. It should be noted that the tensile speed in the tensile test was 10 mm / min and the gauge length was 50 mm. The tensile strength of the test material was determined based on the stress-strain curve obtained by the tensile test. Table 2 shows the tensile strength of the test material after brazing heating.

[0083] Brazing properties Evaluation of brazing properties Figure 2 The microcore test body 2 shown in the figure has two tubes 21 and corrugated fins 22 interposed between the tubes 21. The tubes 21 and the corrugated fins 22 are joined by brazing 23. Specifically, the tubes 21 of this example are made of aluminum alloy, and a 8 g / m 2 In addition, the width of the tube 21 is 16 mm and the length is 40 mm.

[0084] The corrugated fin 22 is made of any of the test materials S1, S2, R1 or R2 shown in Table 1. The corrugated fin 22 has a width of 16 mm, a peak height of 10 mm, and a pitch of 3.0 mm.

[0085] When making the microcore test body 2, first, the corrugated fin 22 is arranged between two tubes 21 to make an assembly (not shown). After the assembly is restrained by a stainless steel fixture, the assembly is immersed in a 10% suspension of a fluoride flux. Then, the assembly is dried to allow the fluoride flux to adhere to the surface of the assembly. The assembly with the fluoride flux adhered is placed in a brazing furnace and maintained at a temperature of 580°C or more and 600°C or less for 3 minutes in a nitrogen atmosphere, thereby forming a brazing joint 23 between the tube 21 and the corrugated fin 22.

[0086] After the brazed micro core test body 2 is cut at the center in the longitudinal direction of the tube 21, it is further cut at the center in the width direction of the tube 21 to expose the cross section of the brazed joint 23. Then, three brazed joints 23 are randomly selected from the plurality of brazed joints 23 formed between the first tube 21a and the corrugated fin 22 in the two tubes 21 (21a, 21b), and the cross-sectional areas of these brazed joints 23 are measured. Similarly, three brazed joints 23 are selected from the plurality of brazed joints 23 formed between the second tube 21b and the corrugated fin 22 in the two tubes 21, and the cross-sectional areas of these brazed joints 23 are measured. The arithmetic mean of the cross-sectional areas of the six brazed joints 23 obtained in the above manner is shown in the "Average fillet weld area" column of Table 2.

[0087] Natural electrode potential after brazing Similar to the evaluation of brazing properties described above, various test bodies are prepared from the microcore test body 2 in the following manner: an internal tube test body for measuring the natural electrode potential inside the tube 21, a tube surface test body for measuring the natural electrode potential on the surface of the tube 21, a fin test body for measuring the natural electrode potential of the corrugated fin 22, and a fillet weld test body for measuring the natural electrode potential of the brazed joint 23.

[0088] When preparing the tube internal test body, first, the corrugated fin 22 is cut off from the microcore test body 2 to remove the first tube 21a. After the surface of the tube 21a is polished to remove the Zn sprayed film, the tube 21a is degreased and cleaned with acetone. Then, a square potential measuring portion with a side of 10 mm is set on the surface of the tube 21a after the Zn sprayed film is removed, and the potential measuring portion and the portion other than one end surface of the tube 21a are covered with a silicone sealant. Through the above steps, the tube internal test body can be obtained.

[0089] When preparing the tube surface test body, first, the corrugated fin 22 is cut off from the microcore test body 2 and the first tube 21a is removed. After the tube 21a is degreased and cleaned with acetone, a portion from a brazing joint 23 at any position to a brazing joint 23 located next to the brazing joint 23 in the Zn sprayed film provided on the surface of the tube 21a is determined, and this portion is used as a potential measurement portion. That is, the potential measurement portion of the tube surface test body is a portion of the surface of the tube 21a corresponding to one pitch of the corrugated fin 22. The potential measurement portion thus set and the portion other than one end surface of the tube 21a are covered with a silicone sealant. Through the above steps, the tube surface test body can be obtained.

[0090] When making the fin test body, first, any one of the fin general parts 221 between the tube 21a and the tube 21b in the corrugated fin 22 is determined, and this part is used as the potential measurement part. Next, the corrugated fin 22 in the microcore test body 2 is cut off so that a part corresponding to one pitch including the potential measurement part remains in the microcore test body 2. Then, after the microcore test body 2 is degreased and cleaned with acetone, the part other than the potential measurement part and any end surface of the tube 21 is covered with a silicone sealant. Through the above steps, the fin test body can be obtained.

[0091] When preparing the fillet weld test body, first, the corrugated fin 22 is cut off from the microcore test body 2 to remove the first tube 21a. Then, the tube 21a is polished to expose the brazing joint 23, and these brazing joints 23 are used as potential measurement parts. Then, after the tube 21a is degreased and cleaned with acetone, the brazing joint 23 and the portion other than one end surface of the tube 21a are covered with a silicone sealant. Through the above steps, a fillet weld test body can be obtained.

[0092] Used in the determination of natural electrode potential Figure 3 The measuring device 3 shown in FIG. 3 comprises: a first container 31 for placing a solution for immersing the test body 4, a second container 32 for placing a solution for immersing the reference electrode 5, a salt bridge 33 for electrically connecting the solution in the first container 31 and the solution in the second container 32, a potentiostat 34 for measuring the potential of the test body 4 relative to the reference electrode 5, and a recording device 35 for recording the measured potential. Figure 3 , the shape of the test body 4 is schematically shown.

[0093] The natural electrode potential was measured as follows. First, a 5% NaCl aqueous solution adjusted to pH 3 using acetic acid was prepared in the first container 31, and a saturated NaCl aqueous solution was prepared in the second container 32. Then, the solution in the first container 31 and the solution in the second container 32 were electrically connected via the salt bridge 33. It should be noted that the temperature of each solution was room temperature.

[0094] Next, the end surface 41 of the tube 21 not covered with the silicone sealant in the test body 4 and the reference electrode 5 are respectively connected to the potentiostat 34. As the reference electrode 5, for example, a saturated calomel electrode (so-called SCE: Saturated Calomel Electrode) can be used.

[0095] In this state, the potential measuring portion 42 of the test body 4 is immersed while stirring the solution in the first container 31, and the reference electrode 5 is immersed in the saturated NaCl aqueous solution in the second container 32, thereby measuring the natural electrode potential of the potential measuring portion 42 of the test body 4 when the reference electrode 5 is used as the reference. Then, the arithmetic mean of the natural electrode potentials of each test body from the time when 10 hours have passed to the time when 15 hours have passed since the start of the measurement is taken as the natural electrode potential of the fin, the fillet weld, the tube surface, and the inside of the tube. Table 3 shows the natural electrode potential of each part. In addition, the "potential difference" column in Table 3 shows the potential difference of the tube surface with respect to the fillet weld.

[0096] Corrosion resistance The micro core test body 2 obtained by the above method is used to perform the SWAAT test according to the method based on ASTM-G85-A3. It should be noted that the test period is either 40 days or 55 days. After the micro core test body after the test is cleaned with acid, the corrosion resistance can be evaluated based on whether the corrugated fin 22 is peeled off from the tube 21.

[0097] In the "Corrosion Resistance" column of Table 3, when the SWAAT test is continued for 55 days without peeling of the corrugated fin 22, a mark "A" is recorded, when the peeling of the corrugated fin 22 does not occur when the SWAAT test is continued for 40 days but peeling of the corrugated fin 22 occurs when the SWAAT test is continued for 55 days, a mark "B" is recorded, and when peeling of the corrugated fin 22 occurs when the SWAAT test is continued for 40 days, a mark "C" is recorded.

[0098] [Table 1]

[0099] [Table 2]

[0100] [Table 3]

[0101] As shown in Table 1, the test materials S1 and S2 have the specific chemical composition. Therefore, as shown in Table 2, the test materials S1 and S2 have excellent brazing properties and have high strength before and after brazing. In addition, as shown in Table 3, the test materials S1 and S2 can maintain the corrosion resistance of the aluminum structure for a long time. Among these test materials, the total content of Fe and Cu in the test material S1 is less than that in the test material S2, so the formability after brazing heating is excellent.

[0102] On the other hand, the Cu content of the test material R1 is less than the specific range, so the liquid phase ratio during brazing heating becomes low. Therefore, as shown in Table 2, the brazing property of the test material R1 is poor compared with the test materials S1 and S2. In addition, since the Cu content of the test material R1 and the total of the Fe content and the Cu content are less than the specific range, as shown in Table 2, the strength of the test material R1 is low compared with the test materials S1 and S2. Moreover, the Cu / Zn value of the test material R1 is less than the specific range, so as shown in Table 3, the potential of the brazing joint is easily excessively reduced. Therefore, the corrosion resistance of the aluminum structure including the test material R1 is poor.

[0103] Similar to the test material R1, the content of Cu in the test material R2 is also less than the specific range, so as shown in Table 2, the test material R2 is also inferior in brazing property compared with the test materials S1 and S2. In addition, the content of Cu in the test material R2 is less than the specific range, so as shown in Table 2, the strength of the test material R2 is lower than that of the test materials S1 and S2. Moreover, the value of Cu / Zn of the test material R2 is less than the specific range, so as shown in Table 3, the potential of the brazing joint is easily excessively reduced. Therefore, the corrosion resistance of the aluminum structure including the test material R2 is poor.

[0104] In the above, the single-layer aluminum alloy material for brazing and the aluminum structure containing the single-layer aluminum alloy material for brazing involved in the present invention are described based on the embodiments, but the specific methods of the single-layer aluminum alloy material for brazing and the aluminum structure containing the single-layer aluminum alloy material for brazing involved in the present invention are not limited to the methods of the embodiments, and the structure can be appropriately changed within the scope without damaging the main purpose of the present invention.

Claims

1. A single-layer aluminum alloy material for brazing, having the following chemical composition: containing Si: 2.0 mass % or more and 3.0 mass % or less, Fe: 0.05 mass % or more and 0.40 mass % or less, Cu: 0.05 mass % or more and 0.25 mass % or less, Mn: 0.8 mass % or more and 1.6 mass % or less, Zn: 1.0 mass % or more and 3.0 mass % or less, the remainder being Al and unavoidable impurities, The ratio of the Fe content to the Cu content is 1.2 or more and 5.0 or less, The total of the Fe content and the Cu content is 0.25 mass % or more and 0.65 mass % or less, The ratio of the Cu content to the Zn content is 0.02 or more and 0.40 or less.

2. The single-layer aluminum alloy material for brazing according to claim 1, wherein: The aluminum alloy material further contains Mg: more than 0 mass % and 2.0 mass % or less.

3. The single-layer aluminum alloy material for brazing according to claim 1 or 2, wherein: The aluminum alloy material further contains one or two or more elements selected from the group consisting of Cr: more than 0 mass % and 0.3 mass % or less, Ti: more than 0 mass % and 0.3 mass % or less, and Zr: more than 0 mass % and 0.3 mass % or less.

4. The single-layer aluminum alloy material for brazing according to any one of claims 1 to 3, wherein The aluminum alloy material also contains one or more elements selected from the group consisting of In: more than 0 mass % and less than 0.3 mass %, Sn: more than 0 mass % and less than 0.3 mass %, V: more than 0 mass % and less than 0.3 mass %, Ni: more than 0 mass % and less than 2.0 mass %, Be: more than 0 mass % and less than 0.3 mass %, Sr: more than 0 mass % and less than 0.3 mass %, Bi: more than 0 mass % and less than 0.3 mass %, and Na: more than 0 mass % and less than 0.3 mass %.

5. An aluminum structure having: The single-layer aluminum alloy material for brazing according to any one of claims 1 to 4; a counterpart material to be joined to the single-layer aluminum alloy material for brazing; and A brazing joint is formed between the single-layer aluminum alloy material for brazing and the counterpart material. A heat exchanger comprising the aluminum structure according to claim 5.

7. A method for producing a single-layer aluminum alloy material for brazing, which is the method for producing a single-layer aluminum alloy material for brazing according to any one of claims 1 to 4, Aluminum scrap is used as at least a part of the casting raw material.

Citation Information

Patent Citations

  • Television receiver

    JP1978037326A